STRATEGI INTERNAL DAN EKSTERNAL DALAM MENGEMBANGKAN AGRO INDUSTRI NILAM (STUDI KASUS KOPERASI INDUSTRI NILAM ACEH BARAT) - Lisma, Yunandar; Baga, Lukman Mohammad; Burhanuddin, Burhanuddin (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2018)
This study aimed to identify the internal and external conditions of the KINA Barat that were influential in the development of patchouli agro-industry and determine the appropriate development strategies for KINA Barat. Data collection was carried out by interview technique and FGD. Data were analyzed using SWOT analysis. The results showed that the strength of the patchouli agro-industry of KINA Barat was the segmented customers, quality products, integrated suppliers, and good relationships with partners. While the weaknesses were the lack of market demand fulfillment, the switching of farmers to other essential plants, the lack of information dissemination media, and the high cost. Opportunities owned KINA Barat among others, were: patchouli market was still wide open, the best essential oil quality is on patchouli, the assistance of the facilitator. The threats of KINA Barat were: a competitor, product substitution, lack of evaluation activity and disturbance in supply. The results obtained that there were some alternative strategies that could be applied:1) SO strategy: increasing customer segmentation, maintaining the quality of KINA West Patchouli oil and enhance cooperation, 2) WO Strategy: maintaining quality and quantity through facilitating facilitation and use of cutting-edge technology, 3) ST Strategy: increasing production, maintaining product quality, improving innovation, expanding supplier networks, and provideing support to supplier networks, and improving evaluation activities, 4) WT Strategy: focusing members to increase production capacity by reducing costs more efficiently, taking preventive measures and improving supporting communication and information infrastructure.